Estimate of compressive strength of an unidirectional composite lamina using cross-ply and angle-ply laminates - M. Scafè; G. Raiteri; A. Brentari; R. Dlacic; E. Troiani; M. P. Falaschetti; E. Besseghini (Fracture and Structural Integrity)
In this work has been estimated the compressive strength of a unidirectional lamina of a carbon/epoxy composite material, using the cross-ply and angle-ply laminates. Over the years various methods have been developed to deduce compressive properties of composite materials reinforced with long fibres. Each of these methods is characterized by a specific way of applying load to the specimen. The method chosen to perform the compression tests is the Wyoming Combined Loading Compression (CLC) Test Method, described in ASTM D 6641 / D 6641M-09. This method presents many advantages, especially: the load application on the specimen (end load combined with shear load), the reproducibility of measurements and the experimental equipment quite simplified. Six different laminates were tested in compressive tests. They were realized by the same unidirectional prepreg, but with different stacking sequences: two cross-ply [0/90]ns, two angle-ply [0/90/±45]ns and two unidirectional laminates [0]ns and [90]ns. The estimate of the compressive strength of the unidirectional laminates at 0°, was done by an indirect analytical method, developed from the classical lamination theory, and which uses a multiplicative parameter known as Back-out Factor (BF). The BF is determined by using the experimental values obtained from compression tests.